Farming systems approach for ensuring food and nutrition security - Panwar, A S; Prusty, A K; Kashyap, Poonam; Singh, M P; Shamim, M; Verma, Nisha; Jat, P C; Kumar, Sunil; Chahal, V P (Indian Farming, 2022)
Farming systems approach proved to be useful tool in enhancing productivity through diversification and intensification as well as profitability for different category of farmers through adoption of improved component technologies along with supplementary and complementary enterprises for optimum use of resources. The holistic approach also aided in meeting household requirement in terms of providing food and nutritional security to the farmers of the locale.